One-step in vivo gene knock-out in porcine embryos using recombinant adeno-associated viruses - Gao, Mengyu; He, YuTing; Zhu, XingLong; Peng, WanLiu; Zhou, YanYan; Deng, Yang; Liao, Guangneng; Ni, Wei; Li, Yi; Gao, Jun; Bu, Hong; Yang, Jiayin; et al. (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Gene-edited pigs have become prominent models for studying human disease mechanisms, gene therapy, and xenotransplantation. CRISPR (clustered regularly interspaced short palindromic repeats)/CRISPR-associated 9 (CRISPR/Cas9) technology is a widely employed tool for generating gene-edited pigs. Nevertheless, delivering CRISPR/Cas9 to pre-implantation embryos has traditionally posed challenges due to its reliance on intricate micromanipulation equipment and specialized techniques, resulting in high costs and time-consuming procedures. This study aims to introduce a novel one-step approach for generating genetically modified pigs by transducing CRISPR/Cas9 components into pre-implantation porcine embryos through oviductal injection of recombinant adeno-associated viruses (rAAV). Methods: We first used rAAV-1, rAAV-6, rAAV-8, rAAV-9 expressing EGFP to screen for rAAV serotypes that efficiently target porcine embryos, and then, to achieve efficient expression of CRISPR/Cas9 in vivo for a short period, we packaged sgRNAs targeting the GHR genes to self-complementary adeno-associated virus (scAAV), and Cas9 proteins to single-stranded adeno-associated virus (ssAAV). The efficiency of porcine embryos -based editing was then validated in vitro. The feasibility of this one-step method to produce gene-edited pigs using rAAV-CRISPR/Cas9 oviductal injection into sows within 24 h of conception was then validated. Results: Our research firstly establishes the efficient delivery of CRISPR/Cas9 to pig zygotes, both in vivo and in vitro, using rAAV6. Successful gene editing in pigs was achieved through oviductal injection of rAAV-CRISPR/Cas9. Conclusion: This method circumvents the intricate procedures involved in in vitro embryo manipulation and embryo transfers, providing a straightforward and cost-effective approach for the production of gene-edited pigs.